The Right to Protest, Freedom of Expression, and Freedom of Association - Cameron, Jamie; Des Rosiers, Nathalie (The Oxford Handbook of the Canadian Constitution, 2017)
Freedom of expression and freedom of association are guaranteed by section 2 of the Charter of Rights and Freedoms. These freedoms are closely related, conceptually and philosophically, but evolved in different directions under the Charter. Whereas section 2(b)’s guarantee of expressive freedom generated a rich jurisprudence across diverse issues, section 2(d)’s attention focused on associational freedom in the context of labour union activities. The authors draw on a pocket of section 2(b) case law on picketing and other labour-related expressive activities to bring these guarantees into comparison. In doing so, they comment on the Supreme Court of Canada’s interpretation of each guarantee, including the constitutionalization of key aspects of labour relations under section 2(d). In addition, the authors critique the Court’s jurisprudence, emphasizing the central importance of protecting protest and dissent activities under both guarantees.